Psychological Readiness to Return to Sport and Return to Sport Rates Are Similar in Patients After Either Bilateral or Unilateral Anterior Cruciate Ligament Reconstruction - Michael Buldo-Licciardi, B.S; Nicole D. Rynecki, M.D; Naina Rao, B.S; Jordan Eskenazi, B.S; Samuel R. Montgomery, Jr., M.D; Zachary I. Li, B.A; Michael Moore, M.D; Michael J. Alaia, M.D; Eric J. Strauss, M.D; Laith M. Jazrawi, M.D; Kirk A. Campbell, M.D (Elsevier, 2024)
Purpose: To compare psychological readiness to return to sport (RTS), RTS rate, level of return, and time to return between patients who underwent bilateral anterior cruciate ligament reconstruction (ACLR) and those who underwent unilateral ACLR. Methods: The electronic medical record at a single academic medical center was queried for patients who underwent ACLR from January 2012 to May 2020. The inclusion criteria were skeletally mature patients who underwent either single or sequential bilateral ACLR and who had undergone either the primary ACLR or second contralateral ACLR at least 2 years earlier. Bilateral ACLRs were matched 1:3 to unilateral reconstructions based on age, sex, and body mass index. Psychological readiness to RTS was assessed using the validated ACL Return to Sport After Injury (ACL-RSI) scale. This, along with time to return and level of RTS, was compared between the 2 cohorts. Results: In total, 170 patients were included, of whom 44 underwent bilateral ACLR and 132 underwent unilateral ACLR. At the time of the first surgical procedure, patients in the unilateral cohort were aged 28.8 ± 9.4 years and those in the bilateral cohort were aged 25.7 ± 9.8 years (P = .06). The average time difference between the first and second surgical procedures was 28.4 ± 22.3 months. There was no difference in psychological readiness to RTS (50.5 in bilateral cohort vs 48.1 in unilateral cohort, P = .66), RTS rate (78.0% in unilateral cohort vs 65.9% in bilateral cohort, P = .16), percentage of return to preinjury sport level (61.2% in unilateral cohort vs 69.0% in bilateral cohort, P = .21), or time to return (41.2 ± 29.3 weeks in unilateral cohort vs 35.2 ± 23.7 weeks in bilateral cohort, P = .31) between the 2 cohorts. Conclusions: Compared with patients who undergo unilateral ACLR, patients who undergo bilateral ACLR are equally as psychologically ready to RTS, showing equal rates of RTS, time to return, and level of return. Level of Evidence: Level III, retrospective cohort study.